EKSEKUSI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 34/PUU-XI/2013 PASCA TERBITNYA SURAT EDARAN MAHKAMAH AGUNG NOMOR 7 TAHUN 2014 - Arafat, Arafat (TANJUNGPURA LAW JOURNAL, 2017)
Contitutional Court of Indonesia Through Decision Number 34/PUU-XI/2013 basically has opened th e space for Request Civil (PK) in Criminal Case is not just once. After that desicion,The Supreme Courtpublish the policy who contradicted with that decision through The Circular of Supreme Court of Indonesia (SEMA) Number. 7 Year 2014 on Reconsideration Request Civil (PK) In Criminal Case.This contradiction make confusion for the law enforcer and justice seekers. The Purpose of this paper is for knowing how legal standing of Constitutional Court of Indonesia Decision and legal standing SEMA in Indonesia Legal system and how the execution Constitutional Court of Indonesia decision number 34/PUU-XI/2013 after SEMA Number. 7 Year 2014 has published. The study in this paper begins with discussing about legal standing of constitusional review on law in indonesian legal system.Next this paper discussing about the circular as a policy rule (beleidsregel). The last ,as key of discussion is about execution of Constitutional Court of Indonesia Decision Number 34/PUU-XI/2013after SEMA Number 7 Year 2014 has published.The conclusions of this paper are : 1) Legal standing of the Constitutional Court of Indonesia decision in indonesia legal syetem can be said to have a degree equivalent to the law. 2) Legal Standing of circular letter is a form of policy rule and is not included in the scope of legislation as regulated in Law no. 12 Year 2011 on the Establishment of Laws and Regulations so that it's not Erga Omnes, but only intended for internal institutional self. 3)The existence of SEMA does not make the Constitutional Court of Indonesia decision to be nonexecutable. Thus Constitutional Court of Indonesia Decision Number 34 / PUU-XI / 2013 which was followed by the justice seeker and executed by the law enforcer.